Climate Change as a Business Risk: : Perspective from Indonesia’s Banking Sector and Regulators - Puspitasari, Indah; Faturohman, Taufiq (The International Journal of Financial Systems, 2026)
Climate change is increasingly recognized as one of the most significant risk that impacts economic stability and the financial system, particularly banking. Although several studies have examined climate change as one of the significant risks that must be considered in the banking business, these studies are generally conducted in developed countries. In developing countries, research on this topic is still relatively limited. This study examines how leading Indonesian banks perceive climate change as a business risk and evaluate their preparedness to align climate risk into their risk management concept, and analyze the regulatory responses from the Financial Services Authority and Bank Indonesia. This research designed as a qualitative study and using a semi-structured interviews with executives form eight major commercial banks and key regulators as respondents. This study uses thematic analysis to identify key patterns in institutional readiness and challenges. The findings indicate that although banks demonstrate a strong awareness of climate-related risks, there are still significant gaps in data availability, methodological tools, and regulatory standardization. Furthermore, the research findings highlight the structural gap between international frameworks and domestic implementation capacity. This study provides three main contributions to the literature. First providing empirical evidence from the banking sector in developing countries, particularly Indonesia. Second, presenting an integrated perspective between banks and regulators in viewing climate risk. Third, identifying the main implementation gap between international standard under Basel Committee on Banking Supervision (BCBS) framework and readiness of Indonesian banking sector.